1995
DOI: 10.1002/bjs.1800820334
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcome for children with hepatoblastoma

Abstract: Between 1981 and 1993, 41 children were treated for hepatoblastoma. Clinical, radiological and pathological data were reviewed retrospectively, focusing on surgical aspects of treatment and outcome. Fourteen children underwent primary resection of the hepatic tumour. One infant with severe congenital anomalies received only palliative treatment. Of 26 with irresectable disease, pulsed cytotoxic chemotherapy (cisplatin and doxorubicin) enabled subsequent surgical excision in 22 and one child with persistent ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 45 publications
2
56
1
Order By: Relevance
“…Children with recurrent tumors or tumors resistant to primary therapy can also be considered for OLTx (7). Advances in imaging technology and chemotherapy have allowed for improvements in the treatment, especially for resections at more advanced stages of disease (6,(8)(9)(10). It has also been observed that patients requiring transplantation tended to be younger than the mean age of presentation (11).…”
Section: Discussionmentioning
confidence: 99%
“…Children with recurrent tumors or tumors resistant to primary therapy can also be considered for OLTx (7). Advances in imaging technology and chemotherapy have allowed for improvements in the treatment, especially for resections at more advanced stages of disease (6,(8)(9)(10). It has also been observed that patients requiring transplantation tended to be younger than the mean age of presentation (11).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the use of preoperative chemotherapy, about half of newly diagnosed hepatoblastomas were considered resectable [15]. In more recent reports only about 30% have been considered resectable at diagnosis, since tumors that are likely to result in significant surgical morbidity with resection are now considered unresectable [45,48]. Chemotherapy has been proven to be effective both in an adjuvant as well as neoadjuvant setting.…”
Section: Treatment Surgerymentioning
confidence: 99%
“…Chemotherapy has been proven to be effective both in an adjuvant as well as neoadjuvant setting. The use of neoadjuvant chemotherapy has resulted in most nonmetastatic hepatoblastomas being resectable [45,48].…”
Section: Treatment Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of microscopic residual disease at the resection margin is not a major adverse determinant of survival. 4,21,22 None of the 11 patients with positive margins in SIOPEL-1 underwent a second resection and all but one was treated by postoperative chemotherapy alone. None developed recurrent tumour and all the survivors were in complete remission 5 years later.…”
Section: Liver Transplantationmentioning
confidence: 99%